Daniella Riggins: capstone - Riggins, Daniella, artist (Colorado State University. Libraries, 2013)
The artist's statement: My works spotlight hues that blend, complement and dance with one another, mimicking the way that visual memories skitter across the mind in an array of colors. Focusing on the chemistry of color, the technicality of weaving threads at the loom, and the poetry of stitching marks onto fabric, I let my unconscious guide the work. Highly saturated colors and layers of thread abstractly replicate cherished events from my childhood. The forms ripple and coil, dimpled and creased like aged memorabilia. Yet they also recall the luster of warm Mexican sunsets and chilled party treats with lots and lots of sprinkles.
Fibers
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.